Lipid-Iron Nanoparticle with a Cell Stress Release Mechanism Combined with a Local Alternating Magnetic Field Enables Site-Activated Drug Release - Medina, Tuula Penate; Gerle, Mirko; Humbert, Jana; Chu, Hanwen; Koepnick, Anna-Lena; Barkmann, Reinhard; Garamus, Vasil M.; Sanz, Beatriz; Purcz, Nicolai; Will, Olga; Appold, Lia; Damm, Timo; et al. (Cancers, 2020)
Simple Summary
CRIS-Team WoS Importer:2021-01-15